Peningkatan Implementasi Learning Management System (LMS) Sebagai Pembelajaran Jarak Jauh Dosen di Era Pandemi Covid-19 - Rizqiyatul Khoiriyah; Gunadi Gunadi; S.B.P. Handhajani; Kusno Suryadi (Universitas Pahlawan Tuanku Tambusai, 2022)
This community service activity is packaged in the form of training and assistance in implementing a learning management system (LMS) for lecturers at Gajayana University, Malang. In the training session, the participants practiced directly how to implement an LMS from start to finish. Then continued mentoring and independent consultation by the companion team of the Information Technology Center (PTI). After the mentoring period is over, the LMS of the lecturers has been successfully filled and implemented in lectures. The end result of this community service activity is an increase in understanding and skills in the implementation of the learning management system (LMS) for lecturers and the achievement of learning content in the LMS that is ready to be used for the next semester's lectures.